2020
DOI: 10.2147/bctt.s279291
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Association of Serum Lipid Levels with Breast Cancer Risks Among Women with Breast Cancer at Felege Hiwot Comprehensive Specialized Hospital, Northwest Ethiopia</p>

Abstract: Background Breast cancer is a malignant condition affecting about 2.1 million women worldwide. Cancer cells have increased the level of cholesterol and facilitate lipid biosynthesis and metabolism. Therefore, there is a need for assessment of serum lipid and its association with breast cancer risks. Methods A comparative cross-sectional study was conducted among women with breast cancer (n=23), benign breast lump (n=68) and apparently healthy control (n=91) at Felege Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
1
9
0
1
Order By: Relevance
“…In this complex process, cells deregulate cholesterol homeostasis, causing intracellular cholesterol accumulation, which is required to maintain their high growth rate. Cancer cells increase the level of cholesterol, facilitating the biosynthesis and metabolism of lipids, and metabolites derived from cholesterol support the progression of cancer and suppress the immune response [ 23 , 24 ]. In our study, the concentration of cholesterol was the highest in the group of animals fed with nanogenistein ( p = 0.02), which may indicate an intense proliferation of tumor cells in this group of rats.…”
Section: Discussionmentioning
confidence: 99%
“…In this complex process, cells deregulate cholesterol homeostasis, causing intracellular cholesterol accumulation, which is required to maintain their high growth rate. Cancer cells increase the level of cholesterol, facilitating the biosynthesis and metabolism of lipids, and metabolites derived from cholesterol support the progression of cancer and suppress the immune response [ 23 , 24 ]. In our study, the concentration of cholesterol was the highest in the group of animals fed with nanogenistein ( p = 0.02), which may indicate an intense proliferation of tumor cells in this group of rats.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal lipid metabolism has been identified as a major metabolic event during cancer development thus leading to alteration in the lipid profile levels (18)(19)(20). Dyslipidemia with low HDL levels and increased TAG, TC, LDL, and VLDL levels raises the risk of developing BC (9,10). Present study evaluated the levels of lipid profile in subjects with and without bc and found a significant rise in TC, LDL, TAG and VLDL, as well as reduced HDL-C levels in the former group, compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity influences the serum lipid profile and causes dyslipidemia, which can negatively affect the integrity of the cells (9). As a result, elevated levels of serum cholesterol (TC), triglycerides (TAG) and abnormality of LDL-C and HDL-C are reported under BC subjects (10). Fatty acid transport and channeling play a significant role in cancer and lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Hal ini dipengaruhi oleh usia paritas pertama, konsumsi alkohol dan indeks masa tubuh yang secara signifikan dikaitkan dengan rendahnya kadar serum HDL. 8 Penelitian yang dilakukan oleh Christoph, et al, tahun 2018 juga menunjukkan bahwa peningkatan kadar LDL memiliki risiko yang lebih tinggi pada kanker payudara dan reseptor estrogen yang positif. Pada penelitian ini juga menyebutkan peningkatan kadar HDL secara genetik dikaitkan dengan risiko estrogen positif yang lebih tinggi pada kanker payudara.…”
Section: Pendahuluanunclassified